Site‐specific methylation patterns of the GAL and GALR1/2 genes in head and neck cancer: Potential utility as biomarkers for prognosis. Issue 3 (1st November 2016) - Misawa, Kiyoshi; Mochizuki, Daiki; Endo, Shiori; Mima, Masato; Misawa, Yuki; Imai, Atsushi; Shinmura, Kazuya; Kanazawa, Takeharu; Carey, Thomas E.; Mineta, Hiroyuki
Abstract : The aim of this study was to evaluate the prognostic value of the promoter methylation status of galanin ( GAL ) and galanin receptor 1/2 ( GALR1/2 ) by assessing their association with disease‐free survival and known prognostic factors in head and neck cancer. We generated methylation profiles of GAL and GALR1/2 in tumor samples obtained from 202 patients with head and neck squamous cell carcinoma (HNSCC); these included 43 hypopharynx, 42 larynx, 59 oral cavity, and 58 oropharynx tumor samples. CpG island hypermethylation status of the three genes was analyzed using quantitative methylation‐specific PCR (Q‐MSP). In order to determine the prognostic value of the methylation status of these genes, the associations between methylation index and various clinical characteristics, especially tumor site, were assessed for tumors from patients with HNSCC. The methylation index was positively correlated with female gender ( P  = 0.008) and disease recurrence ( P  = 0.01) in oral cancer and human papillomavirus (HPV)‐positive ( P  = 0.004) status and disease recurrence ( P  = 0.005) in oropharyngeal cancer. Among patients with oral and oropharyngeal cancer, promoter hypermethylation of GAL, GALR1, or GALR2 was statistically correlated with a decrease in disease‐free survival (log‐rank test, P  = 0.036 and P  = 0.042, respectively). Furthermore, methylation of GAL, GALR1, or GALR2 exhibited the highest association with poor survival (log‐rank test, P  = 0.018) in patients with HPV‐negative oropharyngeal cancers. As such, GAL and GALR1/2 methylation status may serve as an important site‐specific biomarker for prediction of clinical outcome in patients with HNSCC. © 2016 Wiley Periodicals, Inc.